Hydrothermal Synthesis of Flexible Fe-Doped Polyaniline/Dye-Functionalized Carbon Felt Electrode for Supercapacitor Applications - Yazar, Sibel; Arvas, Melih Besir; Sahin, Yucel (WILEY-V C H VERLAG GMBH, 2022)
In this study, Fe-doped polyaniline/dye-functional composite modified carbon felt electrode was synthesized using hydrothermal method and a supercapacitor exhibiting 1.5 V was obtained with 3.0 M KCl aqueous electrolyte. In order to improve supercapacitor performance easily and effectively, the effect of Lanaset Green B (LGB) acidic dye concentration on supercapacitor performance in polyaniline polymerization was investigated. Electrochemical, morphological and structural characterizations of the synthesized electrodes (CFt/Fe-PANI/LGB) were carried out. The results showed that the capacitance increases due to the strong interaction of functional groups between PANI and dye molecules and improves the properties of pseudocapacitive supercapacitors by providing potential redox materials. The CFt/Fe-PANI/LGB(3 mM) electrode displayed a high specific capacitance of 1543 F g(-1) at a scan rate of 5 mV s(-1) in half-cell electrode system. In full-cell, the assembled symmetric supercapacitor has a maximum energy density of 32.7 Wh kg(-1) and power density of 1250 W kg(-1). The supercapacitor electrode and symmetric supercapacitor display retention of capacitance performances 82.3 % and 78.8 % after 2400 and 5000 cycles in 3.0 KCl electrolyte, respectively. CFt/Fe-PANI/LGB(3 mM), flexible, wearable carbon felt electrode material and improved redox behavior of the polymer material play an important role for textile electronics applications.
Keywords: Aniline; aqueous electrolyte; cyclic voltammetry; hydrothermal synthesis; Lanaset green B; supercapacitor; HIGH-PERFORMANCE ELECTRODE; NANOCOMPOSITE; NANOTUBES; FABRICATION; SURFACE; COMPOSITE; REPLICAS; ENERGY; Chemistry